A NEW CRYPTOCRINID GENUS (EOCRINOIDEA, ECHINODERMATA) FROM THE BIOHERM-RELATED VOLKHOV FACIES (LATE ARENIGIAN, ORDOVICIAN), LENINGRAD REGION - Rozhnov S.V.; Fedorov P.V. (My University, 2001)
A new cryplocrinid, Paracryptocrinites bockeliei gen. et sp. nov. (Eocrinoidea, Echinodermata), from the Volkhov (Upper Arenigian, Ordovician) Bioherm-related Facies of the eastern Leningrad region is described. The structure of the bioherms associated with this genus is described.
Keywords: Ordovician; cryplocrinid; Volkhov; Leningrad region; Paleozoic::Ordovician; Палеозой::Ордовикская